Peran Mediasi Kepuasan Kerja pada Model Pengaruh Keadilan Distributif Kompensasi, Keadilan Prosedural Kompensasi, Person-Organizational Fit terhadap Komitmen Afektif (Survei pada Kantor Wilayah Keme - Nur Wahyunianti Dahri (MM UMY, 2015)
Regional Offices of Ministry of Religious Affairs West Sulawesi Province is the government agency tasked to carry out goverment duties and development in the field of religion in the province of West Sulawesi that consistently enforce labor discipline as well as a variety of comprehensive programs to increase employee commitment to the organization. The most important factor to ensure that employees are held to support the organization's commitment is equity compensation, a match between the value of an individual with the organization or person-organization fit (PO-Fit) and job satisfaction. This study was conducted to determine the mediating role of job satisfaction on effect of distributive justice compensation, procedural justice compensation, P-O Fit to organizational commitment. Poupulasi used are all permanent employees in the Ministry of Religious Affairs Regional Office in West Sulawesi province by using purposive sampling technique in sampling.To analyze the data, data analysis techniques used in this study is the method of SEM (Structural Equation Modeling). As expected, result indicated that the Person-organizational Fit (P-O Fit) have a positive Influence on Affective Commitment, Compensation Distributive Justice have a positive Influence on Affective Commitment, Compensation Procedural Justice have a positive Influence on Affective Commitment, Job Satisfaction have a positive influence on Affective Commitment, Person-organization fit (P-O Fit) have a Positive Influence on Job Satisfaction, Compensation Distributive Justice have a positive Influence on Job Satisfaction, Compensation Procedural Justice have a positive Influence on Job Satisfaction, Job Satisfaction is not mediate influence between person-organization fit (PO Fit) on Affective Commitment, Job Satisfaction is not mediate influence between Compensation Distributive Justice on Affective Commitment, Job Satisfaction is not mediate influence between Compensation Procedural Justice on Affective Commitment